Evaluating a clinical ethics committee (CEC) implementation process in an oncological research hospital: protocol for a process evaluation study using normalisation process theory (EvaCEC). Issue 3 (9th March 2023) - Perin, Marta; Magelssen, Morten; Ghirotto, Luca; De Panfilis, Ludovica
Abstract : Introduction: A Clinical Ethics Committee (CEC) is a multi-professional service whose aim is to support healthcare professionals (HPs) and healthcare organisations to deal with the ethical issues of clinical practice. Although CEC are quite common worldwide, their successful implementation in a hospital setting presents many challenges. EVAluating a Clinical Ethics Committee implementation process (EvaCEC) will evaluate the implementation of a CEC in a comprehensive cancer centre in Northern Italy 16 months after its establishment. Methods and analysis: EvaCEC is a mixed-method study with a retrospective quantitative analysis and a prospective qualitative evaluation by a range of data collection tools to enable the triangulation of data sources and analysis. Quantitative data related to the amount of CEC activities will be collected using the CEC's internal databases. Data on the level of knowledge, use and perception of the CEC will be collected through a survey with closed-ended questions disseminated among all the HPs employed at the healthcare centre. Data will be analysed with descriptive statistics. The Normalisation Process Theory (NPT) will be used for the qualitative evaluation to determine whether and how the CEC can be successfully integrated into clinical practice. We will perform one-to-one semistructured interviews and a second online survey with different groups of stakeholders who had different roles in the implementation process of the CEC. Based on NPT concepts, the interviews and the survey will assess the acceptability of the CEC within the local context and needs and expectations to further develop the service. Ethics and dissemination: The protocol has been approved by the local ethics committee. The project is co-chaired by a PhD candidate and by a healthcare researcher with a doctorate in bioethics and expertise in research. Findings will be disseminated widely through peer-reviewed publications, conferences and workshops. Trial registration number: NCT05466292 .